Effect of Nutrition Education and Supplementary Food on the Weight of Wasting Toddlers in Percut Sei Tuan - Sinaga, Junita; Lubis, Zulhaida; Sudaryati, Etti (Jurnal Gizi dan Pangan, 2023)
The aim of the study was to analyze changes in body weight after an intervention. The research design was a quasi-experimental pre- and post-test with a sample of 40 wasting toddlers divided into a group that received tuna meatballs mixed with moringa leaves supplemented with nutrition education and a group that received nutrition education only for 4 weeks. The test results obtained an average weight gain in the first group was 0.79 kg and in the second group was 0.37 kg. The study conclude that meatballs consumption and nutrition education can increase nutritional intake and weight gain in wasted toddlers.